2013
DOI: 10.1111/ejn.12155
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin‐3 innervation of the intergeniculate leaflet of the rat thalamus – neuronal tract‐tracing and in vitro electrophysiological studies

Abstract: Behavioural state is controlled by a range of neural systems that are sensitive to internal and external stimuli. The relaxin-3 and relaxin family peptide receptor 3 (RXFP3) system has emerged as a putative ascending arousal network with putative involvement in regulation of stress responses, neuroendocrine control, feeding and metabolism, circadian activity and cognition. Relaxin-3/γ-aminobutyric acid neuron populations have been identified in the nucleus incertus, pontine raphe nucleus, periaqueductal grey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 68 publications
3
56
0
1
Order By: Relevance
“…Relaxin-3 is primarily expressed in GABA neurons, as reflected by the co-expression of relaxin-3 and glutamate decarboxylase immunoreactivity in the rat nucleus incertus [18], which suggests RXFP3 activation may act to reinforce inhibitory signalling on target neurons. In line with such a role, in vitro studies have revealed activation of the G i/oprotein-coupled RXFP3 by relaxin-3 and truncated analogues produces a dose-dependent inhibition of cellular cAMP levels [14,53], and selective RXFP3 agonist peptides directly hyperpolarize neurons recorded in brain slices [54].…”
Section: Effect Of Icv Rxfp3 Antagonist On Basal Anxiety-like Behaviourmentioning
confidence: 83%
“…Relaxin-3 is primarily expressed in GABA neurons, as reflected by the co-expression of relaxin-3 and glutamate decarboxylase immunoreactivity in the rat nucleus incertus [18], which suggests RXFP3 activation may act to reinforce inhibitory signalling on target neurons. In line with such a role, in vitro studies have revealed activation of the G i/oprotein-coupled RXFP3 by relaxin-3 and truncated analogues produces a dose-dependent inhibition of cellular cAMP levels [14,53], and selective RXFP3 agonist peptides directly hyperpolarize neurons recorded in brain slices [54].…”
Section: Effect Of Icv Rxfp3 Antagonist On Basal Anxiety-like Behaviourmentioning
confidence: 83%
“…Additionally, although evidence is accumulating that RLN3/RXFP3 signalling is able to modulate the same downstream brain areas as monoamine systems, such as the septum [46,47] and extended amygdala [23], it is not known whether RLN3/RXFP3 signalling targets the same or different/neighbouring neurons and circuits to those directly innervated by 5-HT, NA and DA networks. In this regard, the direct effects of RXFP3 activation on individual and populations of brain neurons is largely unknown (but see Blasiak et al [48]). Hence, determining the neurochemical phenotype of RXFP3-positive neurons will be an important advance, but a fully characterised, specific RXFP3 antibody is currently unavailable, preventing traditional double-label immunohistochemical approaches to neurochemically 'phenotype' RXFP3-positive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, the RXFP3 agonist R3/I5 shows diverse effects in cells of the intergeniculate leaflet, with both depolarization and hyperpolarization recorded in different cells from the same preparation (Blasiak et al, 2013). Thus the phenotype of the relaxin-3 recipient neuron and its connections could be crucial to the mode of RXFP3 signaling.…”
Section: Unresolved Pharmacological and Therapeutic Issues And Fumentioning
confidence: 99%